2018
DOI: 10.1007/s00586-017-5455-2
|View full text |Cite
|
Sign up to set email alerts
|

Radiological and functional outcomes of high-grade spondylolisthesis treated by intrasacral fixation, dome resection and circumferential fusion: a retrospective series of 20 consecutive cases with a minimum of 2 years follow-up

Abstract: Intrasacral rod fixation appears to be an effective technique to correct LSA kyphosis, compensatory hyperlordosis and restore global sagittal alignment with a postoperative T1SPi corresponding to the value of the asymptomatic subject and achieve fusion. However, it remains a demanding technique with high risk of transient neurologic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…Therefore, reducing lumbosacral kyphosis and restoring sagittal alignment are major concerns during surgery for high-grade spondylolisthesis. 6 There was a significant reduction in L4 and L5 Severity Index values compared to the preoperative period. However, values remained > 20%, which shows the presence of pelvic retroversion.…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, reducing lumbosacral kyphosis and restoring sagittal alignment are major concerns during surgery for high-grade spondylolisthesis. 6 There was a significant reduction in L4 and L5 Severity Index values compared to the preoperative period. However, values remained > 20%, which shows the presence of pelvic retroversion.…”
Section: Discussionmentioning
confidence: 81%
“…10 In their series, Ferrero et al reported a 70% rate of postoperative neurological complications, the majority of which resolved within 3-6 months of surgery. 11 The Bohlman technique and its various modifications, including the reverse Bohlman technique, have gained traction over the last several years, [12][13][14][15][16] with varying results. For the most part, these techniques have involved decompression and in situ fusion, with little improvement in overall sagittal alignment.…”
Section: Discussionmentioning
confidence: 99%
“… 10 In their series, Ferrero et al reported a 70% rate of postoperative neurological complications, the majority of which resolved within 3–6 months of surgery. 11 …”
Section: Discussionmentioning
confidence: 99%
“…57 Higher mechanical stability and faster symptomatic resolution can be achieved by modifying the Grob technique to involve a trans-discal L5-S1 fixation with L5-S1 pedicle screw instrumentation. 58 To evaluate the efficacy of circumferential fusion, Ferrero et al 59 examined the radiological and functional outcomes of HGS in 20 patients treated by intrasacral fixation, dome resection, and circumferential fusion. At a mean follow-up of 7.2 years, the authors found that lumbosacral angle kyphosis and olisthesis were reduced (658 6 14 versus 998 6 11, P , .001 and 81% 6 19 versus 45% 6 18, P , .001, respectively).…”
Section: Circumferential Interbody Fusionmentioning
confidence: 99%